2003
DOI: 10.1046/j.1365-3083.2003.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Injection in Combination with Electroporation: a Novel Method for Vaccination of Farmed Ruminants

Abstract: Injection of plasmid DNA encoding antigens into rodents followed by electroporation improved the immune response when compared with injection without electroporation (Widera et al. J Immunol 2000;164:4635±40; Zucchelli et al. J Virol 2000;74:11598±607; Kadowaki et al. Vaccine 2000;18:2779±88). The present study describes the extension of this technology to farm animals, by injecting plasmid DNA encoding mycobacterial antigens (MPB70, Ag85B and Hsp65) into the muscles of goats and cattle using two different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Although a few studies have shown that EP can enhance immune responses to a DNA TB vaccine, [40][41][42] no current studies have tested this improved optimized DNA platform in the TB animal model. In this study, we show that all 5 esx optimized constructs we designed induced potent Ag-specific IFN-γ responses to all 15 encoded antigens by ELISpot.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have shown that EP can enhance immune responses to a DNA TB vaccine, [40][41][42] no current studies have tested this improved optimized DNA platform in the TB animal model. In this study, we show that all 5 esx optimized constructs we designed induced potent Ag-specific IFN-γ responses to all 15 encoded antigens by ELISpot.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies performed in larger animal models (4,55,70,71) and nonhuman primates (30,41,44,83) have demonstrated that in vivo EP can markedly augment vaccine antigen-specific humoral immune and CMI responses. However, many of these studies used in vivo EP conditions where the applied voltage was 150 to 250 V/cm.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo electroporation (EP) has proven to be an efficient method for delivering genes into muscle tissue (1,20). The application of electrical pulses to muscle tissue can enhance cell permeability and facilitate pDNA uptake, resulting in 100-to 1,000-fold increases in protein expression (1,39,48,79) and greatly enhanced humoral and cellular immune responses towards the expressed transgene(s) (4,5,10,30,44,47,55,61,64,71,79,83,85). In addition to increasing expression levels, it has been speculated that in vivo EP may result in mild localized tissue damage resulting in the release of cellular components, which might provide a "danger signal" and thus provide an adjuvant effect (46).…”
mentioning
confidence: 99%
“…The lower amount of DNA required as compared with i.m. DNA vaccination, the positive results obtained in large animals (35), along with the availability of devices for electroporation in humans, 7 could make this translation not too unlikely. Enhancement of the protection elicited by DNA electroporation through the concurrence of various accessory signals is being investigated.…”
Section: Discussionmentioning
confidence: 99%